Real-Time Information Systems: A Comparative Economic Analysis - Zani, William M. (Management Science, 1970)
There are several generally accepted suppositions concerning the cost and benefits of real-time information systems. These suppositions expect that real-time systems can generate sufficient benefits to offset the higher costs of processing relative to traditional batch processing systems. The objective of this study was to examine in actual operating environments the generally accepted notions of costs and benefits of real-time systems that were supplied by a computer utility. These suppositions were examined by analyzing the empirical data of six matched firms. The cost and benefits of the information systems of three companies which used a computer utility real-time system were compared to the costs and benefits of three similar companies which used private batch processing systems. The findings of the research were the reverse of expectations. The data analysis strongly suggested that the real-time information did not produce any significant information benefits, but that the real-time data processing costs were less than the comparative batch data processing costs. The primary reason the results differed from expectations is that the real-time information was not fruitfully used. The findings of the study suggest that real-time information system benefits are not gained automatically, but can be achieved only if the systems are meaningfully integrated into the management process.